MOTION GRAPHIC ADVERTISING FOR LIL HAJJ WAL UMROH PROMOTION - Regar, Ahmad Rokhi (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
Dewangga Lil Hajj Wal Umroh in the face of market competition, requires a promotional media with a high level of appeal for its target segmentation, and is able to represent the theme of the pilgrimage properly. Therefore we need a promotional media in the form of Motion Graphic ads. The design of this promotional media advertisement aims to create a promotional media in the form of Motion Graphic advertisement for Dewangga Lil Hajj Wal Umroh, with a persuasive message to increase Dewangga Lil Hajj Wal Umro's customers. The method of making the work of this study project includes five stages: (1) Preparatory / Prelimenary (Research of the Client, Determination of the target audience, and placement of the media); (2) Funding (Material, production, display); (3) Pre Production (Selection of production equipment, making concep art, making storyboards); (4) Production (Creating character assets and environments, moving objects / animatting, dubbing and sound effects, audio and video editing); (5) Post-production (DVD burning, exhibition). The results of this study project were two Dewangga Lil Hajj Wal Umroh Motion Graphic Ads. Work I has a duration of 1 minute 10 seconds with 9 scenes. Work II is 43 seconds long and has 10 scenes. Both of these advertisements have 1280 x 720 px video format.